Towards a results-based monitoring system in public administration in Kosovo - Halili, Ruzhdi (Central European Public Administration Review, 2026)
Purpose: This article aims to analyse the effectiveness of the monitoring system for sector strategies, with particular attention to public administration reform in Kosovo. It seeks to determine whether the monitoring system serves its purpose in measuring performance and the achievement of the results envisaged in sector strategies, thereby supporting evidence-based decision-making, the measurement of institutional performance, and related processes. Design/methodology/approach: The study employs a qualitative research methodology, combining document analysis of monitoring and evaluation reports published by Kosovo institutions during 2024 and 2025, public administration reform strategies, and sector strategies related to the published monitoring and evaluation reports. This method is complemented by the authors’ non-participatory observation and by secondary literature from various international organisations, particularly the OECD, the World Bank and UNDP, as well as from civil society and other domestic stakeholders shaping results-based monitoring in Kosovo. Findings: The study reveals that Kosovo’s public administration has undertaken formal steps to institutionalise a results-based monitoring system in public sector planning, including strategic planning requirements, reporting procedures and general reporting practices. However, challenges remain regarding the quality of the results-based monitoring system and its components, including objectives, indicators, targets and related elements. Reporting, particularly the annual reporting system, is in place and practised. However, most of the analysed reports contain information primarily at the output-indicator level, while some report at the outcome level. Reporting, monitoring and evaluation at the impact level remain overly ambitious. The study also provides evidence that monitoring continues to rely heavily on administrative data, that the use of diversified information-collection methods is limited, and that civil society involvement remains restricted. Academic contribution to the field: The article contributes to the body of literature on public sector monitoring systems, particularly in newly established and transitional public administrations. It provides a country- specific analysis of Kosovo and enriches the comparative regional literature on monitoring and evaluation systems in the Western Balkan countries. The article also links theoretical perspectives with the practical implications of monitoring frameworks in public sector reforms. Originality/significance/value: The article focuses on the analysis of documents that present the monitoring framework in the context of public administration reforms and the country’s European integration process. It is valuable for public administration institutions, policy-makers in Kosovo, civil society stakeholders, donors and development partners, as well as scholars interested in public administration reforms, particularly monitoring systems in public administration.
Keywords: evaluation; Kosovo; public administration reform; RBM; reforma javne uprave; results-based monitoring; rezultatsko usmerjeno spremljanje; sector strategies; sektorske strategije; strategic planning; strateško načrtovanje; vrednotenje